2013
DOI: 10.2337/dc12-0474
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Involvement in Diabetic Cardiomyopathy

Abstract: OBJECTIVETo compare magnetic resonance imaging-derived right ventricular (RV) dimensions and function between men with type 2 diabetes and healthy subjects, and to relate these parameters to left ventricular (LV) dimensions and function.RESEARCH DESIGN AND METHODSRV and LV volumes and functions were assessed in 78 men with uncomplicated type 2 diabetes and 28 healthy men within the same range of age using magnetic resonance imaging. Steady-state free precession sequences were used to assess ventricular dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
4
32
0
1
Order By: Relevance
“…The association between HbA1c and right ventricular function was also not significant in adjusted analyses. While a handful of small studies have shown right ventricular impairments associated with diabetes 41-43 , there is, however, little data about the prognostic value of RV function in a non-disease state and its relationship with HF incidence. Although RV fractional area change is a validated measure of RV systolic function that has been correlated with MRI derived ejection fraction 44,45 and associated with clinical outcomes 46 , it is possible that subclinical impairments in RV function related to dysglycemia cannot be captured by RV fractional area change measurement and may explain the lack of association in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HbA1c and right ventricular function was also not significant in adjusted analyses. While a handful of small studies have shown right ventricular impairments associated with diabetes 41-43 , there is, however, little data about the prognostic value of RV function in a non-disease state and its relationship with HF incidence. Although RV fractional area change is a validated measure of RV systolic function that has been correlated with MRI derived ejection fraction 44,45 and associated with clinical outcomes 46 , it is possible that subclinical impairments in RV function related to dysglycemia cannot be captured by RV fractional area change measurement and may explain the lack of association in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…After indexing for body surface area, RV EDVI was significantly lower. Decreased RV volumes and impaired RV function have also been implicated as components of the diabetic cardiomyopathy phenotype [11]. …”
Section: Discussionmentioning
confidence: 99%
“…In short, RV dimensions and systolic function were assessed by imaging the entire heart in short-axis orientation using electrocardiographically gated breath-hold balanced steady-state free precession imaging. Endocardial contours of the RV were manually drawn in end-diastolic phase and end-systolic phase as previously described [11]. Imaging parameters were as follows: repetition time (TR)=3.3 ms, echo time (TE)=1.67 ms, flip-angle=35°, slice thickness=10 mm, slice gap=0 mm, field of view=400 x 400 mm, reconstructed matrix size=256x 256.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…with diabetes, and in these studies, some reported that cardiac diastolic dysfunction represents an early stage of myocardial damage in patients with diabetes, without any clinical manifestations (8,9). Although RV dysfunction has not been paid due attention in the past, in recent years, researchers have gradually realized that RV dysfunction is relevant and is an independent predictor in a variety of disease states (13,14). Van den Brom reported RV systolic dysfunction in Zucker diabetic fatty rats (15).…”
Section: Discussionmentioning
confidence: 99%